1987
DOI: 10.1038/ki.1987.263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish oil on renal insufficiency in rats with subtotal nephrectomy

Abstract: We studied the effects of fish oil on the progression of renal insufficiency in rats with subtotal nephrectomy. Five weeks after a 1-2/3 nephrectomy, sixteen rats were fed two different diets which differed only in fat composition. Lipid in the control diet was primarily beef tallow; that of the experimental diet, menhaden oil. Fish oil-fed rats had significant increases in plasma creatinines, decreases in urinary PGE2 and accelerated death rates. An additional twelve rats underwent 1-1/3 nephrectomies, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…In the MN rat model, however, Kliem et al [7] found no beneficial effect of low-dose captopril treatment on glomerulosclerosis and proteinuria after 8 months of treatment. One must also note that the nephroprotective effect Schmitz et al [16] found after 9 weeks is in contrast to the observations of Scharschmidt et al [17] who found an increase in proteinuria and glomerulosclerosis after 12 weeks of 21% fish oil diet in the renal ablation model. Also Melhardo et al [18] observed no protective effect of fish oil on glomerulosclerosis and proteinuria.…”
Section: Long Term Trialcontrasting
confidence: 54%
See 1 more Smart Citation
“…In the MN rat model, however, Kliem et al [7] found no beneficial effect of low-dose captopril treatment on glomerulosclerosis and proteinuria after 8 months of treatment. One must also note that the nephroprotective effect Schmitz et al [16] found after 9 weeks is in contrast to the observations of Scharschmidt et al [17] who found an increase in proteinuria and glomerulosclerosis after 12 weeks of 21% fish oil diet in the renal ablation model. Also Melhardo et al [18] observed no protective effect of fish oil on glomerulosclerosis and proteinuria.…”
Section: Long Term Trialcontrasting
confidence: 54%
“…The results of fish oil feeding in rat models of renal injury vary substantially with the model used: whereas in five-sixths nephrectomized rats after 60 days [18] and 12 weeks [17], in heminephrectomized rats after 4 weeks [20], and in obese Zucker rats after 34 weeks [24] no beneficial effects of an EPA-rich diet on the glomerular filtration rate and the progression of renal disease were seen, short-term trials of EPA in models of immunologically induced glomerulosclerosis showed favorable results: the glomerular filtration rate was higher in nephrotoxic serum nephritis with EPA supplementation after 8 weeks [25] and after 12 weeks [23], and proteinuria was lower in Adriamycin-induced glomerular sclerosis after 7 weeks [26]. The trials are, however, difficult to compare not only because of the different rat models used, but also for the varying amounts of polyunsaturated Ω3 fatty acids and tocopherol administered.…”
mentioning
confidence: 99%
“…In adriamycin-induced nephrotic syndrome in rats, a small beneficial effect of fish oil supplementation has also been described [47], It should be noted, however, that in other models of kidney disease, the results of the use of fish oils have been less clear. In the model of subtotal renal abla tion, Scharschmidt et al [48] found that rats supple mented with menhaden oil had a greater decline in renal function, and a greater degree of glomerulosclerosis than did animals fed beef tallow. Other authors, however, have noted beneficial effects of fish oils in the remnant kidney model [49], It has been suggested that the differences in results could be seconday to the toxicity of oxidized fish oil in the former study [50], as an antioxidant used by Barcelli was not used in the Scharschmidt study.…”
Section: Omega-3 Fatty Acid (Fish Oil) Supplementationmentioning
confidence: 99%
“…The reaction could neither be predicted from either the underlying cause of the CRI, nor from the initial severity of renal function loss. Thus fish oil will not be a panacea for renal function preservation in all pa tients with CRI, as Scharschmidt et al [85] already stressed in their animal studies. Longer-term studies directed towards the possible preservation of renal function with fish oil have been reported in patients with IgA nephropathy [86][87][88].…”
Section: Influence On Renal Functionmentioning
confidence: 75%